User surveys support designing a prosthetic wrist that incorporates the Dart Thrower's Motion. (3rd April 2019) - Davidson, Matthew; Bodine, Cathy; Weir, Richard F. ff.
Abstract: Aim: Prosthetic devices are not meeting the needs of people with upper limb amputations. Due to controlsidelimitations, prosthetic wrists cannot yet be fully articulated. This study sought to determine which wrist motions users felt were most important for completing activities of daily living. We specifically invstigated whether adding a combinationof flexion and deviation known as the Dart Thrower's Motion to a prosthetic wrist would help improve functionality. Methods: Fifteen participants with a trans-radial amputation, aged 25–64 years, who use a prosthesis completed an online survey and answered interview questions to determine which types of tasks pose particular challenges. Participants were asked what kinds of improvements they would like to see in a new prosthesis. A subset of five participants were interviewed in-depth to provide further information about difficulties they face using their device. Results: The survey showed that participants had difficulty performing activities of daily living that involve a combination of wrist flexion and deviation known as the "Dart Throwers Motion". Interview responses confirmed that users have difficulty performing these tasks, especially those that require tools. Additionally, users said that they were more interested in having flexion and deviation than rotation in a prosthetic wrist. Conclusion: This research indicates that including the Dart Thrower's Motion in future designs of prosthetic wrists would improve these devices and people with upper limb amputations would be excited to see this improvement in their devices. Implications for Rehabilitation: Over one third of people with upper limb amputations do not use a prosthesis because prosthetic devices do not meet their needs. The number of motions possible in state of the art prosthetic devices is limited by the small number of control sites available. The Dart Thrower?s Motion is a wrist motion used for many activities of daily living but unavailable in commercial prosthetics leading many prosthetics users to have difficulty with these tasks. Prosthetic use, and therefore quality of life, could be improved by including the Dart Thrower's Motion in a prosthesis.